Pembagian Masker Upaya Penanganan Covid-19 di Desa Mandirancan, Kebasen, Banyumas - Adryan Alif Naufal (PT. Gyandharma Global Media, 2025)
The increase in Covid-19 cases in Indonesia is due to the lack of public awareness of the implementation of health protocols, especially the use of masks. The purpose of the Covid-19 KKN activity in Mandirancan Village, Kebasen, Banyumas is to carry out Covid-19 handling efforts in the form of prevention by providing masks. The methods used are Participatory Learning and Action, Participatory Rural Appraisal, and information collection using the interview method. The results of these activities by students have increased the response and awareness of the community in Mandirancan Village, Kebasen, Banyumas in implementing health protocols, especially the use of masks as proof of student devotion to the country.